The visual world of French theory figurations - Wilson, Sarah 1956- (Yale University Press, 2010)
"This book ... focuses on a remarkable series of encounters between the most prominent French philosophers of the 1960s and 1970s-- Sartre, Deleuze, Bourdieu, and Foucault among them-- and the artists of their times, most particularly the protagonists of the Narrative Figuration movement. Each encounter involved either a mutual engagement or the writing of critical texts or catalogue prefaces-- texts that illuminate not only the work of the artists but also the production of the philosopher-writer concerned"--Publisher's description
Keywords: 1900-1999; Geschichte 1900-2000; Geschichte 1960-1979; Geschichte 1900-2010; Art and philosophy; Figurative art; Narrative art (Art movement); Philosophy, French; Art and philosophy / France; Figurative art / France / Paris / 20th century; Philosophy, French / 20th century; Theorie; Kunstkritik; Ästhetik; Figuration narrative; Kunst; Philosophie; Frankreich